Penerapan Model TSTS Untuk Meningkatkan Hasil Belajar Siswa Materi IPA di Sekolah Dasar - Fittriyanti Fittriyanti (Jurnal Didaktika Pendidikan Dasar, 2021)
This study aims to determine the increase in learning outcomes and teacher and student activities in the learning process using the Two Stay Two Stray method on Theme 6 Sub-theme 1 Animal and Plant Diversity. This study used a qualitative approach with the type of classroom action research. The data sources were all students in grade IV SD Negeri 9 Jangka for the 2018/2019 academic year, totaling 16 people. Data were collected through tests, observations, interviews, and field notes. The results showed that the application of Two Stay Two Stray learning can improve student learning outcomes on the material diversity of animals and plants in class IV SD Negeri 9 Term. This can be seen from the results of the final test cycle I obtained a percentage of 62.50 percent and in cycle II increased to 87.50 percent. The activities of teachers and students in the learning process are included in the very good category and students are seen to be active in the implementation of learning. Therefore, it can be concluded that the Two Stay Two Stray model can improve learning outcomes and teacher and student activities on science material in elementary schools.